A Tale of English Language Polytechnic Lecturers’ Decision Making - Abdullah, Suhaily; Abd Majid, Faizah (Dinamika Ilmu: Jurnal Pendidikan, 2016)
Teacher decision making involves a selection of options that leads to thinking processes, underlying teaching in language classroom contexts. Due to this, as a small part of an on-going postgraduate research, this exploratory case study shares the initial findings on the lecturers’ decision-making effects on their classroom orientation. Four lecturers in a local polytechnic were purposively selected as research participants. The primary data was collected through non-participatory classroom observations. Manual constant comparative analysis across the cases was run to obtain the results. Later, the results were triangulated with the responses from informal semi-structured interviews and reflective journal entries. The qualitative analysis revealed that participants did share a similar teaching pattern, i.e. active teaching.  The participants employed learner-focused-orientation approach as their common teaching practice. They worked on their planning decisions as well as their interactive decisions in order to harmonize their teachings to students’ response, proficiency, and attitude. This finding informs some instructional concerns regarding language teaching and learning process in polytechnics’ context (as a Technical and Vocational Education and Training, or TVET, higher education institution in Malaysia) to other English educators in different types and levels of learning institutions.